Trends, magnitude and causes of strikes by workers dependent on an employer in Chile - Armstrong V., Alberto J. (Estudios de Administración, 1997)
This article analyzes the principal characteristics, trends and causes of the strikes that took place in Chile during the period 1979-1995, as well as the most important difierences currently found in the analysis of legal and ilegal strikes, type of industry, unionized and nonunionized strikers, public, private and state-owned companies, and municipal sectors. The number of strikes, workers involved, man-days lost and average duration was used in the analysis. The study is based on the universe of strikes that took place in the above mentioned period, and the sources of inlbnnation were the Directorate of Labor, Carabineros de Chile (police) and the written press. Some of the principal findings that should be mentioned are the important number of strikes that occurred in the public sector -in which they are forbidden-, the increase in the number of illegal strikes and the decrease in the number of legal stiikes in the private sector, and the wage increases and protests against discharge as the main causes of strikes.